Steel slag-phosphogypsum building material and preparation method and application thereof
Patent Information
- Application Number
- CN202410422707.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-04-09
AI Technical Summary
[0006]有鉴于此,本发明提供了一种钢渣-磷石膏建材的制备方法,能够至少一定程度上解决现有磷石膏-钢渣建材强度低、耐久性差、稳定性差、密实度低的问题之一
[0025]1. This invention provides a method for preparing steel slag-phosphogypsum building materials, comprising the following steps: mixing phosphogypsum with steel slag and water, stirring to obtain a phosphogypsum-steel slag slurry; filling the phosphogypsum-steel slag slurry into a mold, compacting and molding it, and then subjecting it to hydration curing to obtain a phosphogypsum-steel slag paste; subjecting the phosphogypsum-steel slag paste to carbon dioxide curing to obtain the final product; wherein: the conditions for carbon dioxide curing include: carbon dioxide pressure of 4MPa-8MPa, and carbon dioxide concentration of 40vol%-90vol%. In this invention, phosphogypsum acts as a catalyst. By mixing phosphogypsum with steel slag, it promotes the rapid dissolution of calcium aluminate in the steel slag to form ettringite. The ettringite then undergoes a carbonation reaction with carbon dioxide to produce monocarbonate or calcite, thereby achieving the effects of fixing carbon dioxide and enhancing the strength of the steel slag. This invention first performs hydration curing, followed by carbon dioxide curing. Hydration curing promotes the hydration reaction of dicalcium silicate (C2S) and tricalcium silicate (C3S) in the steel slag to form hydrated calcium silicate (CSH) gel. This gel has strong cementitious properties and can bond to the cement matrix. The particles in CSH enhance the cohesion and compressive strength of the material, fill pores, and, due to their relatively large volume, can fill the capillary pores and dense voids in the cement matrix during formation, increasing structural density and compressive strength. CSH contains CaO, and its hydration process promotes the transformation of feldspar minerals in cement into more stable species, improving stability. Simultaneously, phosphogypsum can rapidly hydrate to produce needle-like and plate-like calcium sulfate crystals, improving early strength. Furthermore, hydration curing can promote the dissolution of calcium oxide and magnesium oxide to form calcium and magnesium ions, providing more water for the carbonation reaction. The hydration products enhance the initial strength and stability of the material. During carbon dioxide curing, carbon dioxide can react with the aforementioned hydration products to produce carbonates. These carbonates fill the pores of the paste, refining and reducing the pore size, thereby densifying the microstructure of the paste and forming an aggregated carbonate coating layer. The hydration products undergo a carbonation reaction to produce carbonates, and the hydration and carbonation reactions mutually promote each other, forming a dense carbonate substance, which further enhances the strength of the steel slag. The formation of the aggregated carbonate coating layer and the surrounding calcium-poor silicate zone... While carbon dioxide curing can hinder the diffusion of calcium ions from the uncarbonized core of calcium silicate particles, when the phosphogypsum-steel slag paste is damaged, the aggregated carbonate coating and the surrounding calcium-poor silicate zone are destroyed. This allows calcium ions to diffuse from the uncarbonized core of the calcium silicate particles, triggering a re-carbonation reaction to form carbonate precipitates. This replenishes the damaged carbonates and improves the paste's durability. Therefore, carbon dioxide curing of phosphogypsum-steel slag paste can effectively promote carbonate formation, densify the paste's microstructure, and further enhance its strength and durability.
Smart Images

Figure BDA0004782976950000081
Abstract
Description
Technical Field
[0001] This invention relates to the field of industrial waste utilization technology, specifically to a steel slag-phosphogypsum building material and its preparation method and application. Background Technology
[0002] Phosphogypsum is a solid waste residue generated during the treatment of phosphate rock with sulfuric acid in phosphoric acid production. Its main component is CaSO4·2H2O, and it also contains small amounts of harmful impurities such as phosphorus, fluorine, organic matter, and silicon dioxide. The residual phosphoric acid contributes to its high acidity. In the dihydrate wet process for phosphoric acid production, 4-5 tons of phosphogypsum are generated for every ton of phosphoric acid produced. The stockpiling of untreated phosphogypsum not only occupies a large amount of land but also causes serious soil, water, and air pollution. Therefore, it is necessary to find rational ways to utilize phosphogypsum, which can not only achieve the sustainable development of the phosphate fertilizer industry and the high utilization rate of phosphogypsum but also avoid the occupation of valuable land resources and environmental pollution.
[0003] Steel slag is a solid waste produced during the steelmaking process. It consists of various oxides formed by the oxidation of impurities such as silicon, manganese, phosphorus, and sulfur in pig iron during smelting, as well as salts formed by the reaction of these oxides with solvents. Its main component is tricalcium silicate. Producing one ton of crude steel generates 120-140 kg of steel slag waste, but its utilization rate is only about 22.5%. Unutilized steel slag pollutes soil, the environment, and water sources, and occupies land. Therefore, it is necessary to find rational ways to utilize steel slag. This will not only contribute to the sustainable development of the steel industry and the high utilization rate of steel slag, but also avoid the occupation of valuable land resources and environmental pollution, which is of great significance.
[0004] Existing technology discloses a road steel slag-phosphogypsum water-stabilized material and its preparation method, including the following steps: screening the hot-quenched magnetically separated steel tailings to obtain tailings with a particle size of 3mm-10mm; washing the phosphogypsum at least twice, and controlling the water content in the dried phosphogypsum to 15%-20%; mixing stone and sand in a certain proportion to form aggregate; adding the above-mentioned steel tailings, phosphogypsum, aggregate, desulfurization ash, and fine quartz powder into a mixer and mixing evenly; finally adding cement and water for mixing; loading the mixed water-stabilized material into a mold, compacting it using a small-scale pressure machine with vibration, and then curing it in a curing box for 7 days before demolding to obtain the final product. This method solves the environmental pollution problem caused by the large-scale stockpiling of steel tailings and phosphogypsum, reduces quarrying, effectively alleviates resource supply bottlenecks, realizes the comprehensive utilization of steel tailings and phosphogypsum in the region, and promotes the development of a local circular economy. However, the hydration reaction of steel slag is slow. The active ingredients cannot be fully hydrated by curing in a curing box alone, resulting in low strength, poor durability, poor stability and low density.
[0005] In summary, the existing methods for preparing phosphogypsum-steel slag building materials need to be improved. Summary of the Invention
[0006] In view of this, the present invention provides a method for preparing steel slag-phosphogypsum building materials, which can at least partially solve one of the problems of low strength, poor durability, poor stability and low density of existing phosphogypsum-steel slag building materials.
[0007] The present invention also provides a steel slag-phosphogypsum building material prepared by the above method.
[0008] This invention also provides applications of the aforementioned steel slag-phosphogypsum building materials.
[0009] In a first aspect, the present invention provides a method for preparing steel slag-phosphogypsum building materials, comprising the following steps:
[0010] (1) Mix phosphogypsum with steel slag and water, and stir to obtain phosphogypsum-steel slag slurry;
[0011] (2) The phosphogypsum-steel slag slurry is loaded into a mold, compacted and hydrated to obtain phosphogypsum-steel slag slurry.
[0012] (3) The phosphogypsum-steel slag paste is cured with carbon dioxide to obtain the final product; wherein:
[0013] The conditions for carbon dioxide curing include: carbon dioxide pressure of 4 MPa-8 MPa and carbon dioxide concentration of 40 vol%-90 vol%.
[0014] In one optional embodiment, in step (1), phosphogypsum and steel slag are first stirred at a rate of 50 rpm to 80 rpm for 50 s to 70 s, then stirred at a rate of 450 rpm to 550 rpm for 25 s to 35 s, then stirred at a rate of 50 rpm to 80 rpm for 50 s to 70 s, and finally water is added to obtain the phosphogypsum-steel slag slurry.
[0015] In one alternative embodiment, the mass ratio of the phosphogypsum, the steel slag, and the water is 2-4:6-8:1.5-2.5.
[0016] In one optional embodiment, the phosphogypsum is water-washed phosphogypsum, which is obtained by washing the phosphogypsum with water at least three times and then drying it to obtain water-washed phosphogypsum with a water content of 10wt%-15wt%.
[0017] In one optional embodiment, the particle size of the steel slag is 0.5 mm to 5 mm.
[0018] In one optional embodiment, the conditions for hydration curing are: temperature of 20℃-23℃, relative humidity of 88%-92%, and curing time of 12h-72h.
[0019] The conditions for carbon dioxide curing also include: temperature 17℃-23℃, relative humidity 68%-72%, and curing time 12h-168h.
[0020] In one alternative implementation, during the compaction step, the uniaxial load on a single paste is not less than 9 MPa.
[0021] Secondly, the present invention provides a steel slag-phosphogypsum building material prepared by the above preparation method.
[0022] Thirdly, the present invention relates to the application of the above-mentioned steel slag-phosphogypsum building material in concrete, road construction materials, and building materials.
[0023] In one optional embodiment, the water-cement ratio of the phosphogypsum-steel slag slurry is calculated according to the standard consistency water requirement based on GB / T17669.4-1999 "Determination of Physical Properties of Building Gypsum Paste", and is preferably 0.2.
[0024] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0025] 1. This invention provides a method for preparing steel slag-phosphogypsum building materials, comprising the following steps: mixing phosphogypsum with steel slag and water, stirring to obtain a phosphogypsum-steel slag slurry; filling the phosphogypsum-steel slag slurry into a mold, compacting and molding it, and then subjecting it to hydration curing to obtain a phosphogypsum-steel slag paste; subjecting the phosphogypsum-steel slag paste to carbon dioxide curing to obtain the final product; wherein: the conditions for carbon dioxide curing include: carbon dioxide pressure of 4MPa-8MPa, and carbon dioxide concentration of 40vol%-90vol%. In this invention, phosphogypsum acts as a catalyst. By mixing phosphogypsum with steel slag, it promotes the rapid dissolution of calcium aluminate in the steel slag to form ettringite. The ettringite then undergoes a carbonation reaction with carbon dioxide to produce monocarbonate or calcite, thereby achieving the effects of fixing carbon dioxide and enhancing the strength of the steel slag. This invention first performs hydration curing, followed by carbon dioxide curing. Hydration curing promotes the hydration reaction of dicalcium silicate (C2S) and tricalcium silicate (C3S) in the steel slag to form hydrated calcium silicate (CSH) gel. This gel has strong cementitious properties and can bond to the cement matrix. The particles in CSH enhance the cohesion and compressive strength of the material, fill pores, and, due to their relatively large volume, can fill the capillary pores and dense voids in the cement matrix during formation, increasing structural density and compressive strength. CSH contains CaO, and its hydration process promotes the transformation of feldspar minerals in cement into more stable species, improving stability. Simultaneously, phosphogypsum can rapidly hydrate to produce needle-like and plate-like calcium sulfate crystals, improving early strength. Furthermore, hydration curing can promote the dissolution of calcium oxide and magnesium oxide to form calcium and magnesium ions, providing more water for the carbonation reaction. The hydration products enhance the initial strength and stability of the material. During carbon dioxide curing, carbon dioxide can react with the aforementioned hydration products to produce carbonates. These carbonates fill the pores of the paste, refining and reducing the pore size, thereby densifying the microstructure of the paste and forming an aggregated carbonate coating layer. The hydration products undergo a carbonation reaction to produce carbonates, and the hydration and carbonation reactions mutually promote each other, forming a dense carbonate substance, which further enhances the strength of the steel slag. The formation of the aggregated carbonate coating layer and the surrounding calcium-poor silicate zone... While carbon dioxide curing can hinder the diffusion of calcium ions from the uncarbonized core of calcium silicate particles, when the phosphogypsum-steel slag paste is damaged, the aggregated carbonate coating and the surrounding calcium-poor silicate zone are destroyed. This allows calcium ions to diffuse from the uncarbonized core of the calcium silicate particles, triggering a re-carbonation reaction to form carbonate precipitates. This replenishes the damaged carbonates and improves the paste's durability. Therefore, carbon dioxide curing of phosphogypsum-steel slag paste can effectively promote carbonate formation, densify the paste's microstructure, and further enhance its strength and durability.
[0026] 2. This invention provides a method for preparing steel slag-phosphogypsum building materials. First, the mixture is stirred at 50-80 rpm for 50-70 seconds to mix the phosphogypsum and steel slag, ensuring uniform dispersion, reducing the introduction of air bubbles, avoiding localized over-mixing or dust dispersion, and laying a good foundation for subsequent rapid stirring. Then, the mixture is stirred at 450-550 rpm for 25-35 seconds. After the materials are initially mixed evenly, this helps to break up agglomerates in the materials, achieving effective collision and contact between the molecules of each component, promoting more complete chemical reactions within the mixture, improving the homogeneity and completeness of the reaction, generating more hydration products, and improving the mechanical strength, stability, durability, and density of the steel slag-phosphogypsum building materials. Finally, stirring at 50-80 rpm for 50-70 seconds optimizes the microstructure of the mixture, improves fluidity, and reduces air bubbles that may be introduced during stirring, thereby improving the density and uniformity of the steel slag-phosphogypsum. By setting different stirring speeds, this invention can help shorten the production cycle and improve the efficiency of the entire production process while ensuring the quality of material mixing; it can also avoid unnecessary high-energy-consuming operations and reduce energy consumption in the mixing process.
[0027] 3. This invention provides a method for preparing steel slag-phosphogypsum building materials. By limiting the mass ratio of phosphogypsum to steel slag powder to 2-4:6-8, this invention ensures that the mixture has sufficient hydration-active substances such as calcium silicate and calcium sulfate to carry out the hydration reaction. Furthermore, it can effectively promote the chemical reaction in the steel slag during the curing process, enhancing the strength and durability of the material. Thus, this invention can meet the strength and stability requirements of building materials without adding any additional components. At the same time, it improves the utilization rate of phosphogypsum and steel slag, alleviates the pressure on the resource utilization of phosphogypsum and steel slag, reduces the accumulation of industrial waste, and has significant environmental value.
[0028] 4. This invention provides a method for preparing steel slag-phosphogypsum building materials. The phosphogypsum prepared in this invention includes a water washing step before stirring. Water washing removes impurities from the phosphogypsum, such as residual phosphoric acid and other soluble salts, improving the purity and quality of the building materials. Reducing the impurity content in the phosphogypsum allows the calcium aluminate in the steel slag to dissolve rapidly, forming ettringite. The ettringite reacts with carbon dioxide to form monocarbonates or calcite, thereby fixing carbon dioxide and enhancing the strength of the steel slag. This helps improve the chemical stability of the building materials and strengthens their resistance to environmental factors. By controlling the water content of the phosphogypsum, uniform mixing of the materials can be ensured, while promoting the effective hydration and carbonation reactions, resulting in more stable material performance and stronger adaptability.
[0029] 5. This invention provides a method for preparing steel slag-phosphogypsum building materials, limiting the particle size of the treated steel slag to 0.5mm-5mm. The finer particle size provides a larger surface area, which is beneficial to promoting the reaction of active components in the steel slag, thereby improving the early strength and long-term durability of the material. The smaller particle size of the steel slag is easier to distribute evenly in the material, which helps to improve the density and uniformity of the final product, reduce porosity, and improve waterproofness and durability.
[0030] 6. This invention provides a method for preparing steel slag-phosphogypsum building materials. This invention fixes the carbon dioxide emitted during the steelmaking process in steel slag for storage, and prepares high-performance green building materials. It realizes in-situ carbon fixation, makes full use of waste heat energy to accelerate the reaction, has low transportation costs, high solid waste utilization rate, reduces carbon emissions, and is of great significance to ensuring the sustainable development of national resources.
[0031] 7. This invention provides the application of steel slag-phosphogypsum building materials in concrete, road construction materials, and building materials. The steel slag-phosphogypsum building material prepared by this invention can replace cement: Steel slag-phosphogypsum building materials contain components similar to silicate cement, such as dicalcium silicate and tricalcium silicate, but their formation temperature is higher and their hydration rate is slower. By adding a certain amount of phosphogypsum and other admixtures and grinding them, steel slag cement with improved performance can be formed, which can effectively improve the electrical conductivity of concrete. The steel slag-phosphogypsum building material prepared by this invention can be used as a raw material for road construction materials: its volume... Large, blocky, and rough-surfaced, it possesses excellent stability and anti-slip properties, as well as high strength, wear resistance, corrosion resistance, and good durability. Its strong bonding with asphalt makes it suitable for various roadbed materials, engineering backfilling, dam reinforcement, and land reclamation projects, effectively replacing natural crushed stone. The steel slag-phosphogypsum building material prepared by this invention can be used as a building material: suitable for building walls, floors, or roofs, especially in construction projects requiring environmentally friendly and sustainable materials. Because it originates from industrial waste, it can reduce environmental pollution and promote resource recycling. Detailed Implementation
[0032] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0033] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.
[0034] The present invention will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed by the present invention.
[0035] Example 1
[0036] This invention provides a method for preparing steel slag-phosphogypsum building materials, comprising the following steps:
[0037] (1) The steel slag is crushed to obtain steel slag powder with a particle size of 2.5 mm; the phosphogypsum is washed with water 3 times and dried to control the water content of the phosphogypsum at 13% to obtain water-washed phosphogypsum.
[0038] (2) Add 30g of water-washed phosphogypsum and 70g of steel slag powder into a mixer and stir slowly at 60rpm for 60s, then stir quickly at 500rpm for 30s, and then stir slowly at 60rpm for 60s to obtain a phosphogypsum-steel slag mixture.
[0039] (3) Add 20g of water to the phosphogypsum-steel slag mixture obtained in step (2) and stir evenly to obtain phosphogypsum-steel slag slurry;
[0040] (4) The phosphogypsum-steel slag slurry obtained in step (3) is poured into a 40mm×40mm×160mm triple mold and vibrated and leveled. It is then compacted into a single paste under a uniaxial load using a stainless steel mold. The uniaxial load of a single paste is 9MPa. It is then hydrated and cured for 1 day at 20℃ and 90% relative humidity. After molding, the phosphogypsum-steel slag slurry is obtained by demolding.
[0041] (5) The phosphogypsum-steel slag paste obtained in step (4) is placed in a carbon dioxide curing chamber at 20°C, relative humidity of 70%, carbon dioxide pressure of 6MPa, and carbon dioxide concentration of 80vol% for 2 days to obtain phosphogypsum-steel slag building materials.
[0042] Example 2
[0043] This invention provides a method for preparing steel slag-phosphogypsum building materials, comprising the following steps:
[0044] (1) The steel slag is crushed to obtain steel slag powder with a particle size of 0.5 mm; the phosphogypsum is washed with water 3 times and dried to control the water content of the phosphogypsum to 10% to obtain water-washed phosphogypsum.
[0045] (2) Put 20g of water-washed phosphogypsum and 80g of steel slag powder into a mixer and stir slowly at 50rpm for 50s, then stir quickly at 450rpm for 25s, and then stir slowly at 50rpm for 70s to obtain a phosphogypsum-steel slag mixture.
[0046] (3) Add 15g of water to the phosphogypsum-steel slag mixture obtained in step (2) and stir evenly to obtain phosphogypsum-steel slag slurry;
[0047] (4) The phosphogypsum-steel slag slurry obtained in step (3) is poured into a 40mm×40mm×160mm triple mold and vibrated and leveled. It is then compacted into a single paste under a uniaxial load using a stainless steel mold. The uniaxial load of a single paste is 9MPa. It is then hydrated and cured for 1 day at 23℃ and 88% relative humidity. After molding, the phosphogypsum-steel slag slurry is obtained by demolding.
[0048] (5) The phosphogypsum-steel slag paste obtained in step (4) is placed in a carbon dioxide curing chamber at 23°C, relative humidity of 68%, carbon dioxide pressure of 6MPa, and carbon dioxide concentration of 80vol% for 2 days to obtain phosphogypsum-steel slag building materials.
[0049] Example 3
[0050] This invention provides a method for preparing steel slag-phosphogypsum building materials, comprising the following steps:
[0051] (1) The steel slag is crushed to obtain steel slag powder with a particle size of 5 mm; the phosphogypsum is washed with water 3 times and dried to control the water content of the phosphogypsum to 15% to obtain water-washed phosphogypsum.
[0052] (2) Add 40g of water-washed phosphogypsum and 60g of steel slag powder into a mixer and stir slowly at 80rpm for 70s, then stir quickly at 550rpm for 35s, and then stir slowly at 80rpm for 70s to obtain a phosphogypsum-steel slag mixture.
[0053] (3) Add 25g of water to the phosphogypsum-steel slag mixture obtained in step (2) and stir evenly to obtain phosphogypsum-steel slag slurry;
[0054] (4) The phosphogypsum-steel slag slurry obtained in step (3) is poured into a 40mm×40mm×160mm triple mold and vibrated and leveled. It is then compacted into a single paste under a uniaxial load using a stainless steel mold. The uniaxial load of a single paste is 9MPa. It is then hydrated and cured for 1 day at 23℃ and 92% relative humidity. After molding, the phosphogypsum-steel slag slurry is obtained by demolding.
[0055] (5) The phosphogypsum-steel slag paste obtained in step (4) is placed in a carbon dioxide curing chamber at 17°C, relative humidity of 72%, carbon dioxide pressure of 6MPa, and carbon dioxide concentration of 80vol% for 2 days to obtain phosphogypsum-steel slag building materials.
[0056] Comparative Example 1
[0057] This comparative example provides a method for preparing steel slag-phosphogypsum building materials, which is basically the same as the steps in Example 1, except that carbon dioxide curing is performed first, followed by hydration curing.
[0058] Comparative Example 2
[0059] This comparative example provides a method for preparing steel slag-phosphogypsum building materials, which is basically the same as the steps in Example 1, except that in step (5), the carbon dioxide concentration is 95 vol%.
[0060] Comparative Example 3
[0061] This comparative example provides a method for preparing steel slag-phosphogypsum building materials, which is basically the same as the steps in Example 1, except that in step (5), the pressure of carbon dioxide during carbon dioxide curing is 3 MPa.
[0062] Comparative Example 4
[0063] This comparative example provides a method for preparing steel slag-phosphogypsum building materials, which is basically the same as the steps in Example 1, except that 50g of water-washed phosphogypsum and 50g of steel slag powder are added to a mixer and mixed.
[0064] Comparative Example 5
[0065] This comparative example provides a method for preparing steel slag-phosphogypsum building materials, which is basically the same as the steps in Example 1, except that 10g of water-washed phosphogypsum and 90g of steel slag powder are added to a mixer and mixed.
[0066] Comparative Example 6
[0067] This comparative example provides a method for preparing steel slag-phosphogypsum building materials, which is basically the same as the steps in Example 1, except that in step (1), the water-washed phosphogypsum is directly stirred with steel slag powder at 60 rpm for 150 s.
[0068] Comparative Example 7
[0069] This comparative example provides a method for preparing steel slag-phosphogypsum building materials, which is basically the same as the steps in Example 1, except that in step (1), the water-washed phosphogypsum and steel slag powder are directly stirred at 500 rpm for 150 s.
[0070] Experimental Example 1
[0071] The steel slag-phosphogypsum building materials prepared in Examples 1-3 and Comparative Examples 1-7 were subjected to strength tests according to the "Test Method for Compressive Strength of Building Materials" issued by the Standardization Administration of China. The results are shown in the table below; where 1d, 3d, and 7d represent carbon dioxide curing time, respectively.
[0072] Table 1. Performance test results of steel slag-phosphogypsum building materials prepared in each embodiment and comparative example.
[0073]
[0074] As can be seen from the table above, the strength of the steel slag-phosphogypsum building materials prepared in Examples 1-3 increases with the increase of curing time. With the extension of curing time, the internal chemical reaction of the material is more complete, and the porosity is lower and the structure is more compact, thereby improving the compressive strength of the material. This also shows that the preparation method of the present invention can effectively promote the hardening process of the material. By adjusting the ratio of steel slag and phosphogypsum, particle size, and specific parameters of stirring and curing in Examples 1-3 of the present invention, the degree of reaction and compactness of the material can be effectively controlled, thereby affecting its strength and stability. The strength of Comparative Example 1 is relatively low because carbon dioxide curing mainly acts on the surface of the material and its near-surface area. If carbon dioxide curing is carried out first, a dense carbonate layer may be formed. This carbonate layer may hinder the further penetration of water into the interior of the material, thereby affecting the full progress of the hydration reaction and thus affecting the initial strength and compactness development of the material. In Comparative Example 2, when the carbon dioxide concentration is too high, the surface of the material will react rapidly with carbon dioxide to form a layer of calcium carbonate. This layer of calcium carbonate forms a relatively dense layer, which hinders more carbon dioxide from penetrating into the interior of the material. Therefore, the limited carbonation reaction within the material leads to incomplete overall chemical reaction, resulting in poor strength and reduced density. In Comparative Example 3, the reduced pressure during carbon dioxide curing decreases the carbonation depth and the formation of carbonation products, preventing the filling of pores and microcracks in the material, thus increasing porosity and reducing strength. In Comparative Example 4, the high content of washed phosphogypsum prevents sufficient hydration, slowing the hydration reaction and affecting the overall strength development of the mixture. Simultaneously, the washed phosphogypsum forms excessive large pores or unreacted particles, resulting in a loose internal structure and reduced strength. In Comparative Example 5, the high content of steel slag powder means that excessive steel slag does not fully participate in the reaction, leading to insufficient filling of active components in the mixture. Insufficient hydration reaction reduces the overall strength of the material. Simultaneously, steel slag contains easily oxidized metallic components such as iron, manganese, and aluminum. During hydration, these components oxidize to form large-volume products, causing material expansion, creating pores, and generating internal stress, leading to decreased material strength and even cracking. Comparative Example 6 directly mixed water-washed phosphogypsum and steel slag powder at 60 rpm for 150 seconds, resulting in uneven mixing and affecting the completeness of the chemical reaction, thus impacting the final material's performance. Comparative Example 7 directly mixed water-washed phosphogypsum and steel slag powder at 500 rpm for 150 seconds. High-speed mixing introduced excessive air, forming bubbles, resulting in poor density of the steel slag-phosphogypsum building material, which in turn affects its strength.
[0075] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing steel slag-phosphogypsum building materials, characterized in that, Includes the following steps: (1) Mix phosphogypsum with steel slag and water, stir, and obtain phosphogypsum-steel slag slurry; (2) The phosphogypsum-steel slag slurry is loaded into a mold, compacted and hydrated to obtain phosphogypsum-steel slag paste; (3) The phosphogypsum-steel slag paste is cured with carbon dioxide to obtain the final product; wherein: The conditions for carbon dioxide curing include: carbon dioxide pressure of 4-8 MPa and carbon dioxide concentration of 40-90 vol%. The mass ratio of the phosphogypsum, the steel slag, and the water is 2-4:6-8:1.5-2.5; In step (1), phosphogypsum and steel slag are first stirred at a speed of 50 rpm-80 rpm for 50 s-70 s, then stirred at a speed of 450 rpm-550 rpm for 25 s-35 s, then stirred at a speed of 50 rpm-80 rpm for 50 s-70 s, and finally water is added to obtain the phosphogypsum-steel slag slurry.
2. The method for preparing steel slag-phosphogypsum building materials according to claim 1, characterized in that, The phosphogypsum is water-washed phosphogypsum, which is obtained by washing the phosphogypsum with water at least three times and then drying it to obtain water-washed phosphogypsum with a water content of 10wt%-15wt%.
3. The method for preparing steel slag-phosphogypsum building materials according to claim 1, characterized in that, The particle size of the steel slag is 0.5mm-5mm.
4. The method for preparing steel slag-phosphogypsum building materials according to claim 1, characterized in that, The conditions for hydration curing are: temperature of 20℃-23℃, relative humidity of 88%-92%, and curing time of 12h-72h.
5. The method for preparing steel slag-phosphogypsum building materials according to claim 1, characterized in that, The conditions for carbon dioxide curing also include: temperature 17℃-23℃, relative humidity 68%-72%, and curing time 12h-168h.
6. The method for preparing steel slag-phosphogypsum building materials according to claim 1, characterized in that, During the compaction step, the uniaxial load of a single paste is not less than 9 MPa.
7. A steel slag-phosphogypsum building material, characterized in that, It is prepared by the preparation method according to any one of claims 1-6.
8. The application of the steel slag-phosphogypsum building material according to claim 7 in concrete, road construction materials, and building materials.